Upaya Peningkatan Kebersihan Lingkungan, Perilaku Hidup Bersih dan Sehat dalam Peningkatan Kesejahteraan Rakyat - Mukmin Pohan; Novien Rialdy (Institut Riset dan Publikasi Indonesia (IRPI), 2023)
Environmental cleanliness is one of the main factors for a clean, healthy, and comfortable life. Avoiding various diseases is desired by everyone. In maintaining the cleanliness of the environment, not only ourselves, but also the community, and also the government. Observation Method Observation is a data collection tool which is done by systematically observing and recording the symptoms in the village of Sampe Raya. A healthy body can be obtained from exercising regularly, consuming nutritious food and a healthy and clean environment. Sometimes we don't pay attention to a healthy environment because we are busy at work so that the surrounding environment is not kept clean. As a result of an unhealthy environment can cause various diseases, one of which is worrying is dengue fever (DHF) because it can cause death. Environmental cleanliness is a state free from dirt, including dust, garbage and odors.